Storage studies of pineapple titbits - JUBY M. VARGHESE REEBA P. P; Er. Prince M. V (Guide) (Tavanur 2002 Kelappaji college of Agricultural Engineering and Technology)
fresh fruits and vegetables form an important and essential component of human diet.pineapple is one of the choicest multiple fruits which characterise balmy tropical lands.
Storage studies of pineapple titbits